The Relationship Family Support and Depression Level Of Elderly Families With Chronic Diseases During Covid-19 Pandemic In South Sulawesi Province, Indonesia - Gaffar, Indra; Bahtiar, Bahtiar; Permana, Andi Fajrin (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Family of elderly with chronic diseases have potentially dealing with depression. The purpose of this study was to explore the relationship of family support with depression rates of elderly families with chronic diseases during the covid-19 pandemic period. The research was used cross-sectional study. The population was family caregiver of elderly and conducted to 120 families. The data were collected by a purposive sampling technique. Statistical analysis test was used Spearman Rank test. The results of the study showed that there was no correlation between family support and depression levels among elderly families with chronic diseases during the covid-19 pandemic in south Sulawesi (p value = 0.821). Also, weak correlation has been found between family support and depression level among elderly families (0.21). It is hoped that further research is expected to explore deeper family support and coping mechanisms used by families in caring for the elderly with chronic diseases.